HUBUNGAN PENGGUNAAN MEDIA DIGITAL DALAM PEMBELAJARAN TERHADAP KONDISI MENTAL DAN MOTIVASI BELAJAR SISWA: literature review - Novita kenedy; suci fajrina suci fajrina; mega kencana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of digital technology has brought significant changes to the learning process at various levels of education. This article aims to examine the relationship between the use of digital media in learning related to mental health and student learning motivation using a literature review method. Data sources were obtained from various studies, journals, and previous scientific publications over the past five years. The results of the study indicate that the use of digital media has a positive influence on student learning motivation, particularly through the presentation of interactive materials, attractive visuals, creating a lively classroom atmosphere, thus providing easy access to information. However, on the other hand, several studies also show negative impacts that should not be overlooked, such as increased academic anxiety, digital fatigue, and decreased focus due to excessive use of technological devices. Overall, the use of digital media in learning can provide significant benefits for student learning motivation but needs to be balanced with wise management to avoid negative impacts on students' mental health. This article implies that educators need to design learning strategies that are balanced, controlled, and oriented towards students' psychological well-being.